2018
DOI: 10.28978/nesciences.424554
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Composition of the Lionfish (Pterois miles, Bennett 1828), the New Invasive Species of the Mediterranean Sea

Abstract: In this study, the proximate composition of muscle tissue was investigated in lion fish (P. miles), which has a high invasion potency in the Mediterranean. At the same time, the potentials of accumulation of essential and toxic metals in brain, gill, muscle and liver tissues have been examined. The study was carried out with 4 lion fish individuals (1st individual 278 g, 28 cm, 2nd individual 55 g, 19 cm, 3rd individual 68 g, 20 cm, 4th individual 92 g, 22 cm) caught from the Yeşilovacık Bay in 2016. Water, cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Although according to our study, n6/n3 fatty acids of S. lessepsianus was found to be 0.07 in autumn, Özogul and et al (2019) were reported that n6/n3 ratio in Saurida undosquamis were calculated as 0.60 from Bligh and Dyer method in december, 2018. In a similar study, the ratio of n-6/n-3 were found to be 0.06-0.07 for Pterois miles (Ayas et al, 2018).…”
Section: Fatty Acid Levels (Mg/100g)mentioning
confidence: 65%
“…Although according to our study, n6/n3 fatty acids of S. lessepsianus was found to be 0.07 in autumn, Özogul and et al (2019) were reported that n6/n3 ratio in Saurida undosquamis were calculated as 0.60 from Bligh and Dyer method in december, 2018. In a similar study, the ratio of n-6/n-3 were found to be 0.06-0.07 for Pterois miles (Ayas et al, 2018).…”
Section: Fatty Acid Levels (Mg/100g)mentioning
confidence: 65%